2018
DOI: 10.1159/000495482
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Elasticity Regulates Osteocyte Gap Junction Elongation: Involvement of Paxillin in Intracellular Signal Transduction

Abstract: Background/Aims: Osteocytes can sense and respond to extracellular stimuli, including biochemical factors throughout the cell body, dendritic processes, and cilia bending. However, further exploration is required of osteocyte function in response to substrate stiffness, an important passive mechanical cue at the interface between osteocytes and the extracellular matrix, and the deep bio-mechanism in osteocytes involving mechanosensing of cell behavior. Methods: We fabricated silicon-based elastomer polydimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The death rate for a patient that has co-morbidities and gets infected by COVID-19 are higher than a healthy patient. (7,10, 22,24,26,28,29,31,36,37,38,40,42,44,45)…”
Section: Discussionmentioning
confidence: 99%
“…The death rate for a patient that has co-morbidities and gets infected by COVID-19 are higher than a healthy patient. (7,10, 22,24,26,28,29,31,36,37,38,40,42,44,45)…”
Section: Discussionmentioning
confidence: 99%
“…43 Likewise, fibronectin could be regulated by biomaterial stiffnesses in the study of osteocytes, and then the mechanical signal was transmitted through a direct interaction with paxillin, a signal transduction adaptor protein, to regulate osteocyte functions. 10 Similarly, studies into the influences of biomaterial stiffnesses on dental papilla cells (DPCs) identified that the odontogenic differentiation potential of DPCs could be regulated via a fibronectin/paxillin/β-catenin pathway. 44 Based on the previous studies and the observations that biomaterial stiffnesses had a positive correlation to intercellular links among a collective of chondrocytes (Figure 3A,B), to protein levels of fibronectin and type I collagen (Figure 3C,D), we further verified decreased expressions of fibronectin in chondrocytes plated on softer substrates in immunofluorescent images (Figure 3E).…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, our previous studies in osteocytes verified that fibronectin participated in the GJ elongation in response to stiffer substrates. 10,49 Chondrocytes are surrounded by a unique matrix region termed the pericellular matrix (PCM) which is a narrow tissue wedged between the ECM and chondrocytes. 11 Biophysical properties of the PCM, such as stiffness, wettability, and surface roughness, play critical roles in the modulation of cell functions.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors are involved in the regulation of GJIC, e.g., growth factors and changes in extracellular matrix. 37,38 Several growth factors have been confirmed to be involved in the regulation of GJIC, and different growth factors induce distinct and even opposite effects on gap junctions. The effect of epidermal growth factor (EGF) on GJIC of different cell types has been reported.…”
Section: Gap Junctionsmentioning
confidence: 99%